Putusan Cerai Gugat Dan Iddah Istri Dalam Konteks Kehilangan Suami Menurut Hukum Islam Dan Undang-Undang No 1 Tahun 1974 - Tita sirdan maulana; Ahmad Ubaidi Hasbillah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. This research focuses and aims to find out Islamic law, especially thee opinions oof the jurists and Law No. 1 of 1974, resolving cases of missing husbands and determining their iddah period. Thiss researchh is a type of llibrary researchh with a normative qqualitative aproach, which is carried out by analyzing several legal principles, legal theories and legislation related to research. It is known ffrom tthe resultss of this researchh thatt theree are actually no arguments from the Qur'an or special laws that detail cases of missing husbands either in Islamic law or Law No. 1 of 1974. However, in fact, in Islamic law, the results of the fuqaha's ijtihad still provide rights and authority. to a wife suing or complaining to the judge about her loss of her husband, whereas in Laww marrieges it is stated as 0ne of the reas0ns for div0rce. Therefore, the judgee hass the rightt to listen to the statements of the parties concerned and hold a hearing and decide onn thee outcome of the trial in acordance withh the applicable rules. After decision, the number of iddah determined can also be known.